Official Development Assistance In a Colonial Context: Swiss Aid In Palestine (2006-2012) - Ainmelk, Georges (Université d'Ottawa / University of Ottawa, 2016)
This research examines the gap between the socio-political and economic reality of Palestine, under Israeli Occupation, and the perceptions, assumptions and limitations of small aid donors like Switzerland in a colonial context. It looks at how global and Swiss aid is formulated and dispensed to fragile ‘non-states’ like Palestine. My thesis found that aid in general is ineffective, with Swiss aid in particular being modest, lacking robustness and failing to respond to the colonial context that prevents Palestine from profiting the most from international aid. In addition, Swiss aid is afflicted by many shortcomings that have been identified by contemporary research: a large part of aid is tied; consultations with local partners are limited, excluding, by and large, civil society; and time constraints are such that current programs are generally designed on a relatively short-term basis.
Keywords: Swiss aid; Official development assistance; Aid failure; Aid ineffectiveness; Fragile non-state; Palestinian development